Gordura protegida de óleo de palma na dieta para ovinos - Simionatto, Marcio (2016)
It assessed the effects of inclusion of protected fat in the diet of sheep in relation to consumption, digestibility, nitrogen balance ruminal pH, ammonia (N-NH3) and total sugars (CHO). The experiment was conducted at the Unidade de Ensino e Pesquisa de Metabolismo Animal, da Universidade Tecnológica Federal do Paraná, Câmpus Dois Vizinhos, from July to September 2014. It lasted 90 days, with 10 days of adaptation to the environment, with four experimental periods of 20 days, 15 for adaptation to diet and 5 days for the collection of feces, urine and leftovers, these 5 days, 4 days of ruminal fluid samples were collected. 4 male sheep were used, mixed breed, neutered and rumen with an average weight of 50 ± 14 kg, distributed in a Latin square design 4x4, where the data were subjected to analysis of variance and regression due to the inclusion of fat. The animals were fed with concentrate based soybean meal, wheat bran and corn with different levels of inclusion of protected fat, with the control treatment (no addition of protected fat), and the other three with inclusion levels protected fat (2,0%, 4,0% and 6,0% of dry matter) the roughage used was Tifton 85 hay the animals were kept in metabolic cages, with food provided twice a day, at 08:00 and 16:00. No effect of the inclusion of fat intake and digestibility of MS and nutrients, except for the consumption of ether extract positive linear effect (CEE = 22,80 + 11,98x) and positive linear effect for the digestibility in ether extract, being represented by the equation CDEE = 87,45 + 0,61x. Regarding the ruminal pH, there was no effect of treatment with added fat, with an average value of 6,03, but was over time with a cubic effect (P<0,05) in treatment with addition of 2,0% protected fat (pH = 6,07-0,02X-0,01X² - 0,01X³). On the concentration of NNH3 cubic effect was observed (P<0,05) levels of inclusion of fat (N - NH3 = 10,50 + 0,79X + 0,11X² - 0,02X³) and cubic effect versus time for the control treatment with NNH3 = 9,07 - 0,08X - 0,01X² - 0,01X³ equation. Regarding the concentration of total sugars, there was a cubic effect (P<0,05), due to increased levels of fat (CHO = 63,67-2,40X-0,43X²- 0,07X³) and effect a quadratic (P<0,05) as a function of time after feeding for treatment with addition of 2,0% fat protected (CHO= 61,74+ 1,18X+ 0,05X²). It is recommended inclusion of fat protected by up to 6,0% in diets with high concentrate, because even with the observed effects, the final values of the variables were within the expected range, without affecting the development of animals.